2005
DOI: 10.1097/01.mpg.0000182006.90783.8a
|View full text |Cite
|
Sign up to set email alerts
|

Familial Expression of Serological Immune Responses in Pediatric Ibd

Abstract: Background: Although IgA endomysial antibodies (EMA) and tissue transglutaminase (TG) are sensitive and specific serologic tests for the diagnosis of celiac disease, there is limited information on the association of the magnitude of antibody level with the severity of the histological abnormalities of the intestine. Purpose: To determine if EMA and TG titers correlate with the severity of histological changes in patients with celiac disease. Methods: We identified 148 children from our laboratory database tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2009
2009

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…A very recent study has shown that antibodies to OmpC have a strong familial aggregation pattern [62] . Preliminary studies in a pediatric cohort suggest that the quantitative but more so the qualitative expression of immune responses to microbial antigens is increased in the parents of pediatric CD patients, suggesting that the immune dysregulation observed in such patients is a familial trait [63] . Further research in a larger number of parents will increase our understanding of the role of familial expression of serological immune response.…”
Section: Predictor Of Disease Susceptibilitymentioning
confidence: 99%
“…A very recent study has shown that antibodies to OmpC have a strong familial aggregation pattern [62] . Preliminary studies in a pediatric cohort suggest that the quantitative but more so the qualitative expression of immune responses to microbial antigens is increased in the parents of pediatric CD patients, suggesting that the immune dysregulation observed in such patients is a familial trait [63] . Further research in a larger number of parents will increase our understanding of the role of familial expression of serological immune response.…”
Section: Predictor Of Disease Susceptibilitymentioning
confidence: 99%